The Effect of Complex Wall Forms on The Room Acoustics An Experimental Case Study - Agirbas, Asli (eCAADe, 2019)
The complexity of the wall form affects the acoustics of the space. In this study, the effect of the complex form walls produced by nCloth dynamic simulation on the acoustics of an office space was investigated. In this research, reverberation time and Speech Transmission Index (STI) values of the pilot office space with one wall having complex form and the office space with all of the walls as flat were measured by acoustic simulation. As a result of the comparison, it has been found that, within speech intelligibility and reverberation time, the acoustics of the space with one wall having complex form is better than the acoustics of the space with all the walls as flat.
Keywords: NCloth; Acoustics; Complex Forms; Modeling & Simulation